Lactobacillus brevis alleviates the progress of hepatocellular carcinoma and type 2 diabetes in mice model via interplay of gut microflora, bile acid and NOTCH 1 signaling - Chen, Shujia; Han, Ping; Zhang, Qian; Liu, Peiyan; Liu, Jie; Zhao, Lili; Guo, Lianyi; Li, Jia (Frontiers in Immunology, 2023)
Type 2 diabetes (T2DM) clinically exhibits a higher incidence of hepatocellular carcinoma (HCC), contributing to a lousy prognosis in patients harboring both diseases. Microflora-based therapy draws attention with low side effects. Accumulating evidence shows that Lactobacillus brevis can improve blood glucose and body weight of the T2DM mice model and reduce several cancer incidences. However, the therapeutic effect of Lactobacillus brevis in affecting the prognosis of T2DM+HCC remains unknown. In this study, we aim to explore this question via an established T2DM+HCC mice model. We observed a significant alleviation after the probiotic intervention. Lactobacillus brevis improves blood glucose and insulin resistance and ameliorates Mechanically. Combined with a multi-omics approach including 16SrDNA, GC-MS, and RNA-seq, we identified distinct intestinal microflora composition and metabolites after Lactobacillus brevis intervention. Furthermore, we found that Lactobacillus brevis delayed disease progression by regulating MMP9 and NOTCH 1 signaling pathways, potentially through gut microflora and BA interaction. This study indicates that Lactobacillus brevis may improve the prognosis of T2DM + HCC, providing novel therapeutic opportunities via targeting intestinal flora for patients with T2DM+HCC. Key words: Type 2 diabetes; Hepatocellular carcinoma; Lactobacillus brevis; Gut microflora; Bile acids; NOTCH 1 signaling; MMP9